Post-feminist, post-race and post-closet discourses in Critical Studies in Media Communication from 2000-2020. Issue 5 (20th October 2022) - Peters, Wendy
Abstract: This literature review examines 50 scholarly works published in the journal of Critical Studies in Media Communication ( CSMC ) from 2000 to 2020. Each CSMC article has been selected because it employs post-feminist, post-race and/or post-closet as categories to classify media discourse. The publication of 50 articles, comprising 9.8% of research articles in CSMC during this timeframe, testifies to the importance of understanding post- discourses as an analytically and socially significant phenomenon. Summarizing the emergence, antecedents and definitions of each discourse as outlined by CSMC authors, this literature review uniquely maps recurring themes within these 50 articles and across three post- discourses, including: relegating social inequalities to the past; containing an imprint of mainstream civil rights movements while fundamentally reconfiguring them; framing solutions to widespread structural inequalities in terms of individual empowerment; flattering privileged subjects by constituting them as morally good, innocent and caring toward marginalized people; favoring marginalized subjects who perform their empowerment in ways that disavow sexism, racism and homophobia in the present; and holding marginalized groups responsible for contemporary sexism, racism and homophobia. With the aim of enabling students and scholars to better identify and challenge post- discourses in media, I provide an overview of how CSMC authors use post-feminist, post-race and post-closet to categorize media discourse and reveal how post- logics re-center privileged subjects and reassert sexism, racism and homophobia, often in violent and dire terms.